2022
DOI: 10.1002/hon.2981
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of programmed cell death 1 inhibitor maintenance therapy after combined treatment with programmed cell death 1 inhibitors and anti‐CD19‐chimeric antigen receptor T cells in patients with relapsed/refractory diffuse large B‐cell lymphoma and high tumor burden

Abstract: We studied the efficacy and safety of the combined treatment with programmed cell death 1 (PD‐1) inhibitors and anti‐CD19 chimeric antigen receptor (CAR) T‐cell therapy and subsequent PD‐1 inhibitor maintenance treatment in patients with relapsed/refractory (R/R) diffuse large B‐cell lymphoma (DLBCL) and high tumor burden. Forty‐four R/R DLBCL patients with high tumor burden were enrolled in this study. The experimental group of 26 patients received combined therapy with PD‐1 inhibitors and anti‐CD19‐CAR T cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 32 publications
(65 reference statements)
1
5
0
Order By: Relevance
“…Similar phenomena have been observed in other cancers (Burr et al, 2019;Ennishi, Takata, et al, 2019). Therefore, ICBT is usually ineffective against DLBCL, though some studies have reported its successful use in r/ rDLBCL (Xu-Monette et al, 2018;Mu et al, 2022). It is thus speculated that an inflammatory environment favourable to ICBT might exist in some cases of DLBCL.…”
Section: Introductionsupporting
confidence: 53%
“…Similar phenomena have been observed in other cancers (Burr et al, 2019;Ennishi, Takata, et al, 2019). Therefore, ICBT is usually ineffective against DLBCL, though some studies have reported its successful use in r/ rDLBCL (Xu-Monette et al, 2018;Mu et al, 2022). It is thus speculated that an inflammatory environment favourable to ICBT might exist in some cases of DLBCL.…”
Section: Introductionsupporting
confidence: 53%
“…The ORR was 64.71%, but the CR was changed to 64.71%, because some patients who obtained PR in CAR-T therapy become CR after the following radiotherapy. In our previous study [27], R/R DLBCL who had high tumor bulk and at least one tumor with a maximum diameter of ≥ 7.5 cm obtained 62.11% ORR and 38.89% CR in their anti-CD19-CAR T-cell therapy. Compared with our previous study, the R-C group improved ORR and CR, while the C-R group did not improve ORR, but the CR proportion was signi cantly increased.…”
Section: Discussionmentioning
confidence: 88%
“…Mu et al ( 2022) conducted a study involving forty-four patients with relapsed/refractory (R/R) DLBCL to assess the safety and efficacy of combining PD-1 inhibitors with anti-CD19 CAR-T cell therapy, followed by PD-1 inhibitor maintenance therapy in DLBCL patients with high tumor burden (138). These patients were divided into two groups: a combination group of twenty-six patients and a control group of eighteen patients.…”
Section: Cd-19 Directed Car-t Cell Based Combination Immunotherapymentioning
confidence: 99%